Modern Applications of Fiqh in Hajj: Analyzing Islamic Legal Responses to Contemporary Issues - Adnan, Mohammad; Uyuni, Badrah; Mahfuz, Mahfuz (Institute of Education and Social Research, 2024)
This study analyzes the adaptation of Hajj Fiqh to technological developments and social changes in the modern context. By looking at recent developments, including the use of technologies such as mobile applications, information systems, and communication technologies, as well as updates in Hajj procedures and protocols, this study highlights the response of scholars and fatwa institutions to the demands of the times. Recent data shows that there has been an increase in the number of fatwas relevant to the use of technology, health, and the environment in the performance of Hajj. By analyzing the role of clerics, governments, and technologists in addressing the challenges of modern Hajj, this study offers suggestions for further encouraging technological innovation, increasing health and environmental awareness, fostering collaboration among stakeholders, and strengthening the role of religious authorities. It is hoped that the results of this study will help guide decision makers in improving the efficiency, safety, and sustainability of the Hajj in the future.